Size and location of host‐plant shape the spatial pattern of forest insect - Jing, Tian‐Zhong; Cai, Xiao‐Lin; Lu, Hua‐Yang; Dai, Li‐Min; Liu, Li‐Ping; Bai, Li; Li, Xiang; Li, Man‐Yu; Wen, Yi; Han, Qing (Ecological entomology, 2022)
Insect–host relationships can generate spatial patterns. The effect of plant species has been widely investigated, whereas the effect of plant size was ignored. The authors characterized the spatial pattern of the swift moth Endoclita excrescens Butler by combining spatial analysis by distance indices (SADIE) and spatial point pattern analysis (SPPA). Two contiguous plots of monospecific plantations of Manchurian ash Fraxinus mandshurica with different diameters at breast height (DBH) were sampled, and the position, DBH, and count of attack holes of each ash tree were recorded. The aggregation at the landscape scale is far stronger than those at the stand scale. At the landscape scale, trees with small number of bored holes were close to each other at distances of r < 4 m. None of the significant patterns were found at the stand scale. SADIE results showed a strong association between count of attack holes and DBH at the landscape scale, whereas weak association at the stand scale. SPPA results showed that, either at the landscape or stand scale, the locations of ash trees were randomly distributed at small distance, but aggregated at large distance. The counts of holes are only dependent on the point (tree) at small distances (r < 2.5 m) at the landscape scale. These results provide basic information for sampling and precision‐targeted controlling programs. A spatial pattern of forest insect is a non‐additive complex of patterns of insect and host tree. For the swift moth, the aggregation at landscape scale is far stronger than those at stand scale. Host size shapes this spatial pattern of the moth. The distribution of host tree also shapes the spatial pattern of the moth.